The pros and cons of social death fund management by the Malaysian mosque committees - Syed Ibrahim, Sharifah Norhafiza; Jaaffar, Mohd Yassir; Mustafa, Mohd Ariff; Arshad, Yusri (2023)
To explore the pros and cons of managing social or khairat death funds by the mosque committees versus by the registered societies. This study is qualitative, and data was obtained through discussions and interviews with representatives from the relevant authorities and the mosque committees. A thematic analysis was used to analyze the data whereas ATLAS ti 23 was utilized to code and analyze the data. The State Islamic Religious Councils (SIRC) prefer the mosque committees to manage the social death funds. Their arguments revolve around easy-to monitor, stronger accountability, proper and sufficient resources, and ongoing concern matters. Nevertheless, independent societies are perceived to have better procedures and bigger pools of human resources to manage social death funds. Findings from this research are applicable to the sampled rural areas only. This study suggests that the SIRC plays a central role in overseeing the social death funds in rural areas, particularly, those managed by the mosque committees. Nevertheless, community societies are also important as they offer alternative social death funds to rural communities in Malaysia. These societies commonly co-operate with the mosque committees due to all funeral sites are administered by the mosque committees and mosques are equipped with proper equipment and resources for a funeral. Provide empirical evidence for the merits of having social khairat death funds or managed by the mosque committees over local societies.